Teleportation in Virtual Reality; A Mini-Review - Prithul, Aniruddha; Adhanom, Isayas Berhe; Folmer, Eelke (Frontiers in Virtual Reality, 2021)
Teleportation is a widely implemented virtual locomotion technique that allows users to navigate beyond the confines of available tracking space with a low possibility of inducing virtual reality (VR) sickness. This paper provides a comprehensive overview of prior research on teleportation. We report results from user studies that have evaluated teleportation in comparison to other locomotion methods and survey improved versions of teleportation. We identify a number of areas for future research.